2021
DOI: 10.1111/vru.12962
|View full text |Cite
|
Sign up to set email alerts
|

Classification of neoplastic and inflammatory brain disease using MRI texture analysis in 119 dogs

Abstract: Magnetic resonance imaging is the primary method used to diagnose canine glial cell neoplasia and noninfectious inflammatory meningoencephalitis. Subjective differentiation of these diseases can be difficult due to overlapping imaging characteristics. This study utilizes texture analysis (TA) of intra‐axial lesions both as a means to quantitatively differentiate these broad categories of disease and to help identify glial tumor grade/cell type and specific meningoencephalitis subtype in a group of 119 dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Texture analysis (TA) is a significant field of study in medical imaging applications. TA has been utilized in the diagnosis of a variety of cancers [31,[35][36][37]. There is no precise definition of TA, however, it can be described as the analysis of the spatial distribution of patterns that gives the visual appearance of roughness, randomness, smoothness, fluency, etc.…”
Section: Texture Featuresmentioning
confidence: 99%
“…Texture analysis (TA) is a significant field of study in medical imaging applications. TA has been utilized in the diagnosis of a variety of cancers [31,[35][36][37]. There is no precise definition of TA, however, it can be described as the analysis of the spatial distribution of patterns that gives the visual appearance of roughness, randomness, smoothness, fluency, etc.…”
Section: Texture Featuresmentioning
confidence: 99%
“… 1 Granulomatous meningoencephalitis, necrotizing meningoencephalomyelitis, and necrotizing leukoencephalitis are 3 distinct MUO disorders identified by histological evaluation. 2 , 3 , 4 Although the pathogenesis of MUO is unclear, it is most likely multifactorial, combining genetic predisposition with factors triggering an excessive immunologic response. 3 , 4 Tentative diagnosis is based on clinical presentation, inflammatory cerebrospinal fluid (CSF) findings, magnetic resonance imaging (MRI) abnormalities, and lack of an identified infectious agent.…”
Section: Introductionmentioning
confidence: 99%
“…Meningoencephalitis of unknown origin (MUO) is a group of idiopathic, noninfectious, central nervous system (CNS) inflammatory diseases in which a definitive histopathological diagnosis is lacking 1 . Granulomatous meningoencephalitis, necrotizing meningoencephalomyelitis, and necrotizing leukoencephalitis are 3 distinct MUO disorders identified by histological evaluation 2‐4 . Although the pathogenesis of MUO is unclear, it is most likely multifactorial, combining genetic predisposition with factors triggering an excessive immunologic response 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…A common diagnostic dilemma is the differentiation of neoplastic from inflammatory conditions affecting the central nervous system (CNS) of dogs. 15 , 16 , 17 Several studies in dogs have found increased serum or plasma VEGF concentrations in neoplastic versus non‐neoplastic processes outside of the CNS, 7 , 18 , 19 , 20 , 21 , 22 , 23 and several reports have found that increased serum or plasma VEGF concentration suggests a higher tumor grade 18 , 21 or is a poor prognostic indicator in dogs. 7 , 24 , 25 Although plasma VEGF concentration is increased in some dogs with intracranial tumors, 11 cerebrospinal fluid (CSF) is considered to be a more sensitive indicator of CNS disease and is routinely sampled in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…A common diagnostic dilemma is the differentiation of neoplastic from inflammatory conditions affecting the central nervous system (CNS) of dogs 15‐17 . Several studies in dogs have found increased serum or plasma VEGF concentrations in neoplastic versus non‐neoplastic processes outside of the CNS, 7,18‐23 and several reports have found that increased serum or plasma VEGF concentration suggests a higher tumor grade 18,21 or is a poor prognostic indicator in dogs 7,24,25 .…”
Section: Introductionmentioning
confidence: 99%